HOTEL ACCOUNTING STAFF'S PERCEPTION OF THE CHALLENGES OF PREPARING FINANCIAL STATEMENTS: A QUALITATIVE STUDY - Tahlis Farida Novianti; Arifuddin; Syarifuddin (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2026)
This interpretative phenomenological research explores accounting staff perceptions regarding financial reporting challenges within the hospitality sector. Hotel operational complexity with unique characteristics necessitates comprehensive accounting systems capable of managing continuous transactions with elevated accuracy. Qualitative methodology employing in-depth semi-structured interviews was administered to star-rated hotel accounting staff in Makassar to obtain holistic understanding of their experiences. Inductive thematic analysis identified five major themes: cross-departmental financial reporting workflow complexity, data quality challenges and accounting information system integration, temporal pressure and intensive workload during closing periods, competency disparities and capacity development requirements, and perceptions concerning financial reporting quality determinants. Findings reveal that accounting staff encounter substantial psychological pressure originating from high transaction volumes, data system discrepancies with physical documentation, and intricate interdepartmental coordination. Developed coping strategies encompass intensive team collaboration, multilayer verification, and technological adaptation. Practical implications emphasize the urgency of continuous training, personnel augmentation, and system integration optimization to enhance hotel financial reporting reliability.